Derivation and validation of an epigenetic frailty risk score in population-based cohorts of older adults - Li, Xiangwei; Delerue, Thomas; Schöttker, Ben; Holleczek, Bernd; Grill, Eva; Peters, Annette; Waldenberger, Melanie; Thorand, Barbara; Brenner, Hermann (Nature communications, 2022)
DNA methylation (DNAm) patterns in peripheral blood have been shown to be associated with aging related health outcomes. We perform an epigenome-wide screening to identify CpGs related to frailty, defined by a frailty index (FI), in a large population-based cohort of older adults from Germany, the ESTHER study. Sixty-five CpGs are identified as frailty related methylation loci. Using LASSO regression, 20 CpGs are selected to derive a DNAm based algorithm for predicting frailty, the epigenetic frailty risk score (eFRS). The eFRS exhibits strong associations with frailty at baseline and after up to five-years of follow-up independently of established frailty risk factors. These associations are confirmed in another independent population-based cohort study, the KORA-Age study, conducted in older adults. In conclusion, we identify 65 CpGs as frailty-related loci, of which 20 CpGs are used to calculate the eFRS with predictive performance for frailty over long-term follow-up. Frailty is associated with an increased risk for negative health outcomes in older populations, and being able to predict frailty could facilitate prevention measures. By performing an epigenome-wide screen, the authors derived a DNA methylation based measure for frailty which can predict both prevalence and longer-term incidence of frailty.